Assessing genotoxic effects in fish from a marine protected area influenced by former mining activities and other stressors - Gusso-Choueri, Paloma Kachel [UNESP]; Choueri, Rodrigo Brasil; Santos, Gustavo Souza; de Araújo, Giuliana Seraphim [UNESP]; Cruz, Ana Carolina Feitosa [UNESP]; Stremel, Tatiana; de Campos, Sandro Xavier; Cestari, Marta Margarete; Ribeiro, Ciro Alberto Oliveira; de Sousa Abessa, Denis Moledo [UNESP] (Elsevier, 2016)
The goal of the current study was to evaluate different genotoxicity tools in order to assess a marine protected area (MPA) affected by former mining activities and urban settlements. A catfish (Cathorops spixii) was analyzed for genotoxic effects at the (i) molecular and at the (ii) chromosomal levels. Through factor analysis, genotoxicity was found to be linked to levels of metals bioaccumulated and PAH metabolites in the bile. Micronucleus and nuclear alteration were less vulnerable to the effects of confounding factors in mildly contaminated areas since they were more frequently associated with bioaccumulated metals than the DNA analysis. The different genotoxicity responses allowed for the identification of sources of pollution in the MPA. This approach was important for detecting environmental risks related to genotoxic contaminants in a mildly contaminated MPA.
Keywords: Biomarkers; Environmental quality assessment; Estuary; Genotoxicity; Multivariate approach; Weight of evidence